WORKLOAD SPIKES COMBINED WITH HIGH CUMULATIVE LOAD IS ASSOCIATED WITH INCREASED INJURY RISK IN ELITE RUGBY SEVENS PLAYERS. Issue 4 (1st February 2017) - West, Stephen; Williams, Sean; Cross, Matthew; Howells, Dan; Mobed, Remi; Kemp, Simon; Stokes, Keith
Abstract : Background: Match and training demands differ between seven and fifteen-a-side rugby. The association between training load and injury risk has not been examined in elite Rugby Sevens. Objective: To explore the association between training load measures and injury risk in elite Rugby Sevens players. Design: Two-season (2014/15 and 2015/16) prospective cohort study. Setting: The England men's Rugby Sevens squad. Participants: 42 players (31 players followed over one-season, 11 players over two-seasons). Assessment of Risk Factors: Training loads were recorded for all sessions using the session-Rating of Perceived Exertion method. A generalised linear mixed effects model examined the association between training load measures and injury risk in the subsequent week. The acute:chronic workload variable (one-week load divided by four-week average load) was parsed into tertiles: low=<1.15; medium=1.15–1.45; high=>1.45. Main Outcome Measurements: Injury and the relative risk (RR) associated with increases in training load measures. Results: 152 training and 30 match injuries were recorded. The incidence rate was 91/1000 player-match-hours (90% CI: 68–123) and 14/1000 player-training-hours (90% CI: 12–16). Mean severity (day's absence) of injuries was 31 days during matches and 21 days during training. There was a substantial interaction between four-week cumulative load and acute:chronic workloads, such that typically high versus typically low four-week cumulative loads (i.e., a 7140 AU difference) coupled with high acute:chronic workloads were clearly associated with injury risk (RR: 2.08, 90% CI 1.17–3.68). This effect was unclear in the low (RR: 1.02, 90% CI: 0.62–1.68) and medium (RR: 1.44, 90% CI: 0.81–2.55) acute:chronic workload ranges. Conclusions: The injury incidence rate in elite Rugby Sevens training is substantially higher than in the 15-a-side game. The coupling of high cumulative loads with high acute:chronic workloads was associated with an increased injury risk, therefore practitioners should avoid high acute:chronic workloads during periods of high cumulative load.